The Influence of Financial Performance, Corporate Governance, and Bank Size on Environmental Costs of Islamic Banks for the 2021-2023 Period - Hanip, Sipa Muhamad; Ridha, Noorsyah Adi Noer (Journal of Applied Islamic Economics and Finance, 2025)
This study investigates the effect of financial performance, corporate governance, and bank size on environmental costs in Islamic Commercial Banks (BUS) in Indonesia from 2021 to 2023. Financial performance is proxied by Return on Assets (ROA), corporate governance by the number of Sharia Supervisory Board (DPS) members, and bank size by total assets. Environmental cost is measured through CSR expenditures related to environmental initiatives. The research employs a quantitative approach using panel data regression and secondary data from the annual reports of 10 BUS, analyzed with EViews 13. The results reveal that the three variables collectively have a significant impact on environmental costs. However, individually, only the DPS variable significantly affects environmental spending, while ROA and bank size do not. These findings highlight the pivotal role of Sharia governance in promoting environmentally responsible behavior in Islamic banks.